Integrated contingency model of strategic management accounting: exploratory study in portuguese companies - Salvador, Anaísa (2020)
This study aims to replicate the study by Cadez and Guilding (2008) in the context of large portuguese companies. The main objective of this study is to test relationships between strategic choices, market orientation, company size, accountant participation, strategic management accounting and performance. In particular, we intend to test possible mediating effects of the participation of accountants and the use of strategic management accounting. Data collection will be done through a questionnaire survey of large portuguese companies. Descriptive statistics, correlation coefficients and analysis of structural equations will be used. In this sense, it is intended to obtain results comparable to those obtained from the study by Cadez and Guilding (2008), in order to seek to expand details on contingency theory and strategic management accounting.